2007
DOI: 10.1111/j.1551-2916.2007.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Structure Analysis of BaTiO3 Ceramics by Synchrotron X‐Ray Diffraction

Abstract: The shell thickness of a BaTiO3 ceramic with a core–shell structure has been measured by means of synchrotron X‐ray diffraction (XRD). BaTiO3 ceramic is known from transmission electron microscope (TEM)/energy dispersive X‐ray spectroscopy (EDS) observations to have an inhomogeneous microstructure with cores of a pure BaTiO3 and shells doped with additives. It is also known, from XRD observations, that the BaTiO3 cores have a tetragonal lattice structure and the shells are pseudocubic. We have estimated the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 9 publications
2
36
1
Order By: Relevance
“…It is, therefore, difficult to differentiate the effects of the two parameters, the thickness and composition of the shell, on dielectric-temperature properties. Yasukawa et al [25] observed a similar variation of dielectric-temperature properties with increased ball milling time. In their case, however, as the ball milling time increases, the chemistry in the shell as well as grain size vary considerably.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…It is, therefore, difficult to differentiate the effects of the two parameters, the thickness and composition of the shell, on dielectric-temperature properties. Yasukawa et al [25] observed a similar variation of dielectric-temperature properties with increased ball milling time. In their case, however, as the ball milling time increases, the chemistry in the shell as well as grain size vary considerably.…”
Section: Introductionmentioning
confidence: 63%
“…It was reported that the temperature stability is improved with a reduction of shell thickness. In those previous studies, however, additional effects due to factors such as different chemistry in the shell [10,26,27] and difference in grain size [25,27] might have influenced the results. In addition, the variation of the core/shell fraction is estimated mostly by indirect methods, such as EDS [10,26,27] and synchrotron X-ray diffraction [25].…”
Section: Concentration Of Y (At%)mentioning
confidence: 72%
See 2 more Smart Citations
“…As the endothermic peak is absent in the DSC curves of the present work, it is clear that the percentage tetragonality in the synthesized powders is below 64%. Though high-permittivity and reliability is associated with the tetragonal structure, the sharp transition of permittivity at T c restricts its application [40]. Highpermittivity and stable dielectric constant for a large temperature range is required of a BaTiO 3 ceramic capacitor [41].…”
Section: Tga Dsc Analysismentioning
confidence: 99%